What the Buddha taught - Walpola Rāhula (New York Grove Press : Distributed by Random House, 1974)
Clarifies the fundamental principles of Buddhist doctrine by explicating the original Pali text of the Tipitaka.
Keywords: Gautama Buddha -- Teachings Buddhism -- Doctrines. Gautama Buddha. Teachings. Buddhism